AI Chatbot as an Effective English Teaching Partner for University Students - Satiti, Laras Hayu; Fauziati, Endang; Seytaningsih, Endang (CV. Inara, 2024)
This study investigated the effectiveness of an AI chatbot for improving English language skills among Indonesian university students. In order to address the research question, the researchers conducted an analysis of responses to a 20-item questionnaire distributed via Google Form among a sample of 95 university students. The survey was conducted to evaluate student perceptions of the chatbot's usability, language accuracy, feedback quality, and overall strengths. The findings revealed high student satisfaction with all aspects of the chatbot. Students agreed that the chatbot was user-friendly, understood their questions, provided helpful feedback, and offered valuable learning opportunities. These results align with previous research on the effectiveness of chatbots in enhancing English language proficiency. The study suggests that AI chatbots can be a beneficial tool for both independent language practice and supplementing classroom instruction. The chatbot's ability to personalise learning experiences and adapt to individual needs contributes to improved student engagement and language acquisition. This research adds to the growing body of evidence supporting the use of AI chatbots in computer-assisted language learning (CALL). Future research could investigate the effectiveness of the chatbot for learners with varying proficiency levels.